Model-informed precision dosing to optimise immunosuppressive therapy in renal transplantation. Issue 11 (November 2021) - Zwart, Tom C.; Guchelaar, Henk-Jan; van der Boog, Paul J.M.; Swen, Jesse J.; van Gelder, Teun; de Fijter, Johan W.; Moes, Dirk Jan A.R.
Highlights: Immunosuppression is key for sustained graft survival after renal transplantation. Optimally balanced immunosuppressive therapy is challenged by PK variability. MIPD may aid to achieve personalised, effective and safe immunosuppressive therapy. Various MIPD models are available but their clinical application remains limited. Harmonised models and informative biomarkers are key to advance personalized dosing. Abstract: Immunosuppressive therapy is pivotal for sustained allograft and patient survival after renal transplantation. However, optimally balanced immunosuppressive therapy is challenged by between-patient and within-patient pharmacokinetic (PK) variability. This could warrant the application of personalised dosing strategies to optimise individual patient outcomes. Pharmacometrics, the science that investigates the xenobiotic–biotic interplay using computer-aided mathematical modelling, provides options to describe and quantify this PK variability and enables identification of patient characteristics affecting immunosuppressant PK and treatment outcomes. Here, we review and critically appraise the available pharmacometric model-informed dosing solutions for the typical immunosuppressants in modern renal transplantation, to guide their initial and subsequent dosing.